A ππ∗ State Enables Photoaccumulation of Charges on a π-Extended Dipyridophenazine Ligand in a Ru(II) Polypyridine Complex - Schindler, Julian; Zhang, Ying; Traber, Philipp; Lefebvre, Jean-Francois; Kupfer, Stephan; Demeunynck, Martine; Gräfe, Stefanie; Chavarot-Kerlidou, Murielle; Dietzek, Benjamin (Journal of Physical Chemistry C, 2018)
The π-extended dipyrido[3,2-a:2′,3′-c]phenazine (dppz) ligand of the Ru(II) complex [Ru(bpy)2(oxo-dppqp)](PF6)2 (oxo-dppqp = dipyrido[3,2-a:2′,3′-c]pyrido[2″,3″-4,5,6]quinolino[2,3-h]phenazin-15-one, bpy = 2,2′-bipyridine) enables the mononuclear complex for visible-light-driven accumulation of two electrons on a single ligand structure. Although this has been shown before, the excited-state physics underlying this promising feature are exploited in this work. The photophysics of the complex was investigated by excitation-wavelength-dependent resonance Raman and transient absorption spectroscopy in combination with time-dependent density functional theory. The results show that excitation with visible light leads to the population of the two excited-state branches: (i) the population of a short-lived 3MLCT state in which the excess electronic density is localized on the pyridoquinolinone moiety of the extended ligand (τ = 105 ps) and (ii) the population of a more long-lived 3ππ∗ state (τ = 9 ns). Notably, the long-lived 3ππ∗ state rather than a 3MLCT state is prone to reductive quenching by the sacrificial electron donor and, hence, presents the critical excited-state intermediate in the photochemical charge accumulation experiments.
CRIS-Team Scopus Importer:2023-04-20